1999
DOI: 10.1016/s0954-6111(99)90104-x
|View full text |Cite
|
Sign up to set email alerts
|

Volume calibration alone may be misleading

Abstract: The use of spirometry is becoming more and more widespread in non-laboratory situations such as general practice or occupational medicine. In these non-laboratory situations, volume calibration with a 3000 ml syringe is often the only feasible method to ensure that the spirometer produces valid and reproducible data. Sophisticated equipment to calibrate forced manoeuvres with standard waveforms are not present. In this study, we assessed whether volumetric calibration is a guarantee for valid and comparable sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 4 publications
0
11
2
Order By: Relevance
“…Moreover, the observed differences increase with the increase in the value of the pulmonary function parameters [4,7,9]. van den Boom et al [5 ]also reported on this nonlinearity of modern, compact spirometers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the observed differences increase with the increase in the value of the pulmonary function parameters [4,7,9]. van den Boom et al [5 ]also reported on this nonlinearity of modern, compact spirometers.…”
Section: Introductionmentioning
confidence: 99%
“…Volume calibration alone is insufficient. The validity of the measurements should be examined by organizing a series of parallel measurements compared with a reference standard [4,5]. Third, the reliability of the measurements can also be tested from a broader perspective with regard to the kind of changes that need to be measured or the kind of decisions that can be taken based on the measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, regular use of a calibration syringe would be desirable, even while this does not guarantee that the spirometer readings from patients’ forced maneuvers are indeed accurate [15,33]. Regular biological calibration (by a healthy test operator in the practice) [34,35] is probably the most feasible option.…”
Section: Discussionmentioning
confidence: 99%
“…Calibration with a syringe provides information on volume accuracy, and does not guarantee accurate volume or flow readings during forced breathing manoeuvres. 25 Frequent 'biological calibration' by a healthy test subject may be a valid alternative for primary care, 26 but more studies on this matter are needed.…”
Section: Accuracy Linearity and Reproducibility Of Electronic Spirommentioning
confidence: 99%